Agitation in Cognitive Disorders: Use of the National Alzheimer's Coordinating Center Uniform Data Set (NACC‐UDS) to Evaluate the International Psychogeriatric Association Definition. (20th December 2022) - Sano, Mary; Zhu, Carolyn W; Neugroschl, Judith A.; Grossman, Hillel; Schimming, Corbett; Aloysi, Amy
Abstract: Background: The consensus‐based definition of agitation by the International Psychogeriatric Association (IPA) has not been evaluated in community‐based samples who are not preselected for behavioral disturbances. Here we use a well‐characterized cohort of community‐dwelling older individuals with cognitive impairment to assess the IPA criteria associated with agitation to validate the construction of this diagnostic entity Method: We used the National Alzheimer Coordinating Center Unified Data Set (NACC‐UDS) to select a cognitively impaired cohort across etiological diagnoses, excluding those with a primary psychiatric etiology (IPA criteria A). We used this dataset to evaluate the IPA consensus‐based provisional definition of agitation in cognitive impairment. We used clinician diagnosis of agitation as a gold standard in those with MCI and dementia and the Neuropsychiatric Inventory–Questionnaire (NPI‐Q) algorithm to define agitation symptoms (IPA Criteria B); Standardized assessments of function (including Functional Assessment Scale and CDR Sum of Boxes) were used to assess excess social/functional disability (IPA Criteria C). We examined patterns of psychiatric comorbidities to determine if they were consistent with IPA criteria (IPA Criteria D). Result: We identified a cognitively impaired cohort (N = 19, 424), across multiple etiologies (AD = 73.7%, FTLD = 9.7%, LBD = 6.8% and vascular brain injury = 3.5%). Mean (SD) age was 72.7 (10.1) years, 77.0% were non‐Hispanic White, 11.1% non‐Hispanic Black, 8.3% Hispanic, with an average of 14.7(3.7) years of education. Mean (SD) MMSE = 22.0(6.4), FAQ = 12.7(9.5), and GDS = 2.8(2.8). Clinician judgement of agitation was present in 15.7% of the sample. Those with agitation were younger, more likely to be male, had slightly lower educational levels and were more likely to be from under‐represented groups. 38.6% had agitation by NPI algorithm, with high agreement with clinician judgement. More than 84% of those with clinician judgment of agitation and 74% of those meeting the NPI algorithm demonstrated excess social/functional disability. Psychiatric comorbidities were present in 38% of the sample without evidence of agitation, and were higher in those with agitation (56% to 82%, depending on agitation definition). Conclusion: Agitation ranges between 15 and 38% in those with cognitive impairment. The pattern of excess disability and presence of comorbid psychiatric symptoms in this well characterized dataset is consistent with IPA published criteria.